GAMBARAN KUALITAS HIDUP PADA PASIEN PENYAKIT JANTUNG KORONER DI POLI JANTUNG RSUD PROVINSI NTB - Sintha Puspitasari; Baiq Leny Nopitasari; Putri Izzul Durrani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Coronary Heart Disease (CHD) is the leading cause of death worldwide, including in Indonesia. It significantly affects patients’ physical, psychological, social, and spiritual well-being, thereby influencing their quality of life. This study aimed to describe the quality of life of CHD patients at the Cardiology Clinic of NTB Provincial Hospital. This was a descriptive observational study with a cross-sectional design. A total of 41 respondents were recruited using accidental sampling during December 2024–January 2025. Quality of life was assessed using the MacNew questionnaire, which covers physical, emotional, and social domains. Data were analyzed descriptively using univariate analysis. Most respondents were aged 56–65 years, male, had high school education, were unemployed, and had comorbidities. The majority (95.1%) of patients had good quality of life, while 4.9% had poor quality of life. The highest mean score was in the emotional domain (75.86%), followed by social (72.90%) and physical (71.52%). Conclusion: Most CHD patients in NTB Provincial Hospital demonstrated good quality of life, with emotional well-being being the highest-scoring domain.